Lessons in aging from Myc knockout mouse models - Prochownik, Edward V.; Wang, Huabo (Frontiers in Cell and Developmental Biology, 2023)
Despite MYC being among the most intensively studied oncogenes, its role in normal development has not been determined as Myc−/− mice do not survival beyond mid-gestation. Myc ± mice live longer than their wild-type counterparts and are slower to accumulate many age-related phenotypes. However, Myc haplo-insufficiency likely conceals other important phenotypes as many high-affinity Myc targets genes continue to be regulated normally. By delaying Myc inactivation until after birth it has recently been possible to study the consequences of its near-complete total body loss and thus to infer its normal function. Against expectation, these “MycKO” mice lived significantly longer than control wild-type mice but manifested a marked premature aging phenotype. This seemingly paradoxical behavior was potentially explained by a >3-fold lower lifetime incidence of cancer, normally the most common cause of death in mice and often Myc-driven. Myc loss accelerated the accumulation of numerous “Aging Hallmarks”, including the loss of mitochondrial and ribosomal structural and functional integrity, the generation of reactive oxygen species, the acquisition of genotoxic damage, the detrimental rewiring of metabolism and the onset of senescence. In both mice and humans, normal aging in many tissues was accompaniued by the downregulation of Myc and the loss of Myc target gene regulation. Unlike most mouse models of premature aging, which are based on monogenic disorders of DNA damage recognition and repair, the MycKO mouse model directly impacts most Aging Hallmarks and may therefore more faithfully replicate the normal aging process of both mice and humans. It further establishes that the strong association between aging and cancer can be genetically separated and is maintained by a single gene.